A internacionalização do mercado imobiliário de Salvador e Região Metropolitana - REIS, Luiz Fernando de Carvalho (2007)
This essay aims to determine the effects caused in the real estate market in Salvador and it’s outskirts, due to the increasing participation of international corporations in such market. This sectorial descriptive research encloses several of the franchised companies to the Associação de Dirigentes de Empresas do Mercado Imobiliário da Bahia (ADEMI). This research will take place in Salvador and it’s districts, including Mata de São João, where several real estate companies, objects of research, are located. Data collection will be made through interviews with managers of entities which represent their classes (CEF, ADEMI, SINDUSCON, CRECI e SENAI), with the objective of identifiying and selecting the main elements that influence market competition. In addition, managers of local and international companies of the sector will be interviewed seeking to point out to what extent the internationalization of the real estate market interferes in Salvador’s and RMS’ sectorial competition. It is concluded that the arrival of international companies had a strong impact on the market.